Multispectral study of tuna cultivation to determine the NDVI, CWSI and SAVI indexes from Sentinel 2A images, in Guano canton, Chimborazo province, Ecuador - Chamorro Sevilla, Hernán Eriberto; Erazo, Alex (Enfoque UTE, 2019)
This work evaluates the Normalized Differential Vegetation Index (NDVI), Soil Adjusted Vegetation Index (SAVI), and Water Stress Index (CWSI) in tuna crops, located in the Guano Canton of Chimborazo Province, Ecuador. The area of interest (AOI) included the parishes of San Andres and Guano, in which the texture of the soil was determined with the existing data in Ecuador's National Information System (SNI), a satellite image of Sentinel 2A from June 16 2018 was used. Raster functions were applied to obtain an approximate and referential mean of NDVI, the reflectance received from both the soil and the tuna crop (SAVI) and the perspiration corresponding to the water stress (CSWI) of the tuna plots. Finally, we obtained approximate and referential NDVI data with a value of 0.31, SAVI values reflecting soil and crop data, and a very low CWSI, showing that perspiration is minimal, so it can be concluded that drip irrigation is a suitable technique for increasing tuna production.